Diversity of Tarekat Communities and Social Changes in Indonesian History - Dudung Abdurahman (Universitas Islam Negeri Sunan Kalijaga, 2018)
Islam as a religious system is generally based on three principal teachings called as aqidah (theology), syari'ah (law), and tasawwuf (Sufism, moral and spiritual). Each thought and the Islamic expertise have also established Muslim communities that demonstrate the diversity of social and religious history in various regions on the spread of Islam. In the history of the spread of Islam in Indonesia, particularly the Sufis always showed a significant role in each period of social change. Therefore, further discussion of this paper will be based on the development of tarekat communities. The historical facts in this study are presented gradually based on the unique cases in each period. The tarekat communities in Nusantara in the early period of Islam, which is the 13th century until the 17th century, have established the religious system patterned on the diversity of doctrine, thought, and tradition that is acculturative with various cultures of the local society in Nusantara. Then they developed during the Dutch colonial period in the 18th century and the 19th century. Besides contributing in the Islam religious founding, they also contributed in the patriotism struggle and even protested in the form of rebellion towards the Dutch colonial. The Sufis from various tarekat streams displayed antagonistic of political acts towards the Colonial government policies. It was developed at the beginning of the 20th century, which is the period of nationalism and of Islamic reform movements. The social force of tarekat people became an indicator of the religion revival that was very influencing towards the nationalism movement in Indonesia. The last one, it has been developing on the independence day of Indonesia, which is called the contemporary period, until today. The tarekat people have built a community system variously based on the principle of beliefs and various ritual activities. The tarekat people always develop, modify, and actualize the tasawwuf teachings and the tarekat practice, mainly in order to complete the spirituality and morality improvement of the society. The tarekat people’s contributions are very helpful for the society in general in order to fulfill the mental necessity. Their religiosity is also strategic enough to be used as a control media for the moral life of the nation.